Penanganan Sampah Secara Kolaboratif antara Masyarakat dan Petugas Penanganan Prasarana dan Sarana Umum (PPSU) Tingkat Kelurahan (Kasus Penanganan Sampah di Kelurahan Jembatan Lima Kecamatan Tambora Kota Administrasi Jakarta Barat) - Tampubolon, Edwin Rinaldo; Sri Rahayu, Amy Yayuk (Jurnal Inspirasi, 2019)
Abstract Waste management is one form of public service from the government. On the other hand the community must also participate and collaborate with the government in the implementation, decision making, and supervision of waste handling. By using a descriptive qualitative approach, this study answers how collaborative governance processes in handling waste between community self-help and Public Facility Maintenance Officers (PPSU) and the factors that influence it. The results of the study show that collaborative waste management processes have been built with the involvement of government and non-government actors, there are a division of authority, collaboration between community self-help, community waste bank organization, public facility maintenance (PPSU) and the jakarta barat Environtment agency in collaboration with the private sector. Dialogue, trust, understanding, commitment have been established to achieve temporary result. Private involvement in collaborative governance processes is still limited to the stages of waste sorting activities. Research also found that this collaborative process was not perfect. factors that influence, among others are the low understanding of the community about sorting waste, the people’s mindset that is still traditional in handling waste, lack of motivation from garbage officers, and less optimal infrastructure and management of garbage truck transportation. For this reason, socialization, more intensive counseling, assistance to change community behavior and innovation in stimulating active participation from the community are needed. Keywords : Collaborative Governance, Waste Management, waste sorting, waste collection, waste transportation, Facility Maintenance Officers (PPSU)